An Investigation of the Funding Operations of Zimbabwe Geological Survey Department - Machengete, Garikai F (2017)
The research sought to investigate the funding operations of the Geological Survey Department, under Ministry of Mines and Mining Development. The study was motivated by the fact that the department has been experiencing an increasing operational funding deficit. There has been a trend of perpetual rise in costs while revenue has been decreasing between 2010 and 2013. The Geological Survey department is gradually losing capacity to generate new information. There has not been any field mapping projects for a long time. The department has been incurring high costs in repairs and maintenance of obsolete Property, Plant and Equipment while employment costs arising from lost man hours of unfulfilled trips have also been fueling the rise in funding deficit. Restocking of the library has become very difficult. Records in the department show that geological bulletins and maps sold by the department are out of print and those available in stock are out-dated. Consequently their demand has fallen for the same period. Continual rise in deficit since 2010 has made it very difficult for the department to replace aged assets let alone upgrading the existing ones. This study sought to investigate the causes. A comprehensive review of literature related to the topic under study was carried out in the interest of obtaining data on what other authors who carried out studies on the same research area have contributed in order to obtain the relevant information. Qualitative and quantitative research methods were used to collect data related to the research. Questionnaires and personal interviews were the research instruments used to collect data that was used to obtain research findings that were later analyzed to fulfill the research objectives. The researcher recommended practical solutions that could address the department’s funding challenges.